Studies on mixed-species colonies of honeybees, Apis cerana and Apis mellifera - Yang, Ming-Xian (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
The honeybees Apis cerana and Apis mellifera are derived from the same ancestral base about two million years ago. With speciation and evolution, they have acquired many advanced living skills in common, but have also evolved very different living strategies due to different distributions. This thesis is an intensive study of the biology of the mixed-species colonies of these species, the aims of which were to investigate their behavioural relationships and uncover the evolutionary conserved features of their behaviours subsequent to speciation. The results show that the two species can form a stable society to perform normal tasks. First, workers of both species in the mixed-colonies could form the typical retinue behaviour to hetero-species queens, thus indicating that queen pheromones could be spread to and by both species. Secondly, both species did not show significantly different ovarian activation under hetero-species queens, suggesting that the queen pheromones more likely play a role of "honest signal" rather than a "repression" substance in the honeybee colonies. Thirdly, both species could mutually decode each other's waggle dances, with unexpectedly low misunderstanding; revealing that the dance language in a dark environment is quite adaptive for cavity-nesting honeybees. Fourthly, workers of both species could cooperate with each other in comb construction, although the combs they built contain many irregular cells. Interestingly, A. cerana workers could be stimulated by A. mellifera workers to perform this task, thus confirming self-organization theory in the colony. Fifthly, A. mellifera workers behaved more "defectively" in thermoregulation, but perhaps because A. cerana workers are more sensitive to changes in hive temperature. Given these differences in strategy, A. mellifera workers' performance might in fact reduce conflicts. Lastly, when faced with threats of predatory wasps, both species engaged in aggressive defence. Although they did not learn from each other's responses, species-specific strategies were adopted by each of them so that the defence of the mixed-colonies is very effective. I conclude that the two species can adapt to each other's efforts and task allocation is reasonably organized allowing mixed-species colonies to reach stability. These results suggest that all of the social behaviours discussed here were highly conserved following speciation. This thesis could provide some clues for the study of honeybee evolution from open-nesting to the transition of cavity-nesting.
Keywords: Bees; Apis cerana; Honeybee; Honeybee -- Behavior; Bee culture; Honeybee -- Physiology; Insect societies; Animal communication; Bees -- Nests